Cochlear implantation in unilateral deaf subjects associated with ipsilateral tinnitus - Buechner, Andreas; Brendel, Martina; Lesinski-Schiedat, Anke; Wenzel, Gentiana; Frohne-Buechner, Carolin; Jaeger, Burkard; Lenarz, Thomas (Otology & neurotology, 2010)
In subjects who are deaf and who also have tinnitus in the affected ear, tinnitus treatments based on acoustic input are impossible. On the other hand, tinnitus suppression using electric stimulation has been reported to be successful. Therefore, a study was initiated to investigate the potential of cochlear implantation (CI) in unilateral deaf subjects regarding tinnitus suppression, device acceptance, and restoration of spatial hearing. Five subjects with severe to profound unilateral deafness having also ipsilateral tinnitus were enrolled. In monthly visits, the speech processor program was optimized, and the hearing performance as well as tinnitus were monitored. In addition, it was investigated whether the CI improves hearing in adverse listening situations when combined with the normal hearing side. In 3 participants, the tinnitus was significantly suppressed while wearing the device. In the other 2 participants, the tinnitus could be reduced in certain situations. Speech perception tests revealed a significant benefit with the CI in combination with the normal-hearing side for 3 participants. All participants accepted the device in a clinical setting; adaptation of the frequency allocation was not required. Improvements were found regarding the hearing and the tinnitus. Not all participants benefit from the CI to the same degree and in the same situations.The results indicate that cochlear implantation in subjects with unilateral severe to profound hearing loss and ipsilateral tinnitus may be beneficial on a case-to-case basis. Further work needs to be performed to define the appropriate indication criteria.